2015
DOI: 10.1111/cea.12590
|View full text |Cite|
|
Sign up to set email alerts
|

Molecular‐based allergy diagnosis of allergic bronchopulmonary aspergillosis in Aspergillus fumigatus‐sensitized Japanese patients

Abstract: SummaryBackgroundDistinguishing between patients with allergic bronchopulmonary aspergillosis (ABPA) and Aspergillus fumigatus (Af)‐sensitized asthmatic patients without ABPA is sometimes difficult owing to the IgE‐cross‐reactivity between Af and other fungal allergens.ObjectiveTo establish the usefulness of molecular‐based allergy diagnostics using allergen components from Af in distinguishing ABPA from Af‐sensitized asthma without ABPA.MethodsSera from Japanese patients with ABPA (n = 53) and Af‐sensitized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
45
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 45 publications
3
45
1
1
Order By: Relevance
“…Current reports on IgG responses to commercially available allergens from A. fumigatus are scarce and address mainly ABPA patients with an asthmatic background . Our team found that IgG4 responses to A. fumigatus allergens did not distinguish between A. fumigatus ‐sensitized CF patients and active ABPA .…”
Section: Component‐resolved Diagnostics: Molecular Aspects Of the Hummentioning
confidence: 82%
See 4 more Smart Citations
“…Current reports on IgG responses to commercially available allergens from A. fumigatus are scarce and address mainly ABPA patients with an asthmatic background . Our team found that IgG4 responses to A. fumigatus allergens did not distinguish between A. fumigatus ‐sensitized CF patients and active ABPA .…”
Section: Component‐resolved Diagnostics: Molecular Aspects Of the Hummentioning
confidence: 82%
“…This explains the tentative proposal of “a raised level of sIgE to A. fumigatus ” in more recent papers. Abundant experimental data support this view, but a widely validated threshold is lacking. Disparate cutoff values have been reported in the literature, from 1.91 kUA/L to “class 2 or more” to 29.8 kUA/L .…”
Section: Why Should Immunological Criteria For Abpa Diagnosis Be Updamentioning
confidence: 99%
See 3 more Smart Citations